Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/cea.12893
|View full text |Cite
|
Sign up to set email alerts
|

Memory and multitasking performance during acute allergic inflammation in seasonal allergic rhinitis

Abstract: Our findings suggest that SAR has a differentiated and complex impact on cognitive functions, which should be considered in the management of SAR symptoms. They also call attention to the importance of selecting sensitive measures and carefully interpreting cognitive outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…However, a survey in the Middle East found that 10% of responders had AR [9]. Although AR is not life-threatening, AR affects the quality of life, and is a common risk factor for multiple airway conditions [10][11][12][13]. AR and asthma can be viewed as two corresponding airway diseases as they have common traits [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, a survey in the Middle East found that 10% of responders had AR [9]. Although AR is not life-threatening, AR affects the quality of life, and is a common risk factor for multiple airway conditions [10][11][12][13]. AR and asthma can be viewed as two corresponding airway diseases as they have common traits [14].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, they translate into substantial economic burdens because of the increased demands on health services and reduced workplace productivity due to absenteeism [11][12][13][14]. Further, symptomatic allergic rhinitis, is also associated with impaired learning and reduced examination performance [15,16]. Allergic diseases overall have been estimated to cost the Australian economy $30 billion per year [17].…”
Section: Introduction and Purposementioning
confidence: 99%
“…163 This study highlighted the knowledge gap regarding the actions of various inflammatory mediators of allergic disease on the central nervous system. 163 This study highlighted the knowledge gap regarding the actions of various inflammatory mediators of allergic disease on the central nervous system.…”
Section: Rhinitis Allergic Mechanismsmentioning
confidence: 95%
“…Other work pointed to an adverse effect of seasonal allergic rhinitis on cognitive functions related to memory and multitasking. 163 This study highlighted the knowledge gap regarding the actions of various inflammatory mediators of allergic disease on the central nervous system.…”
Section: Rhinitis Allergic Mechanismsmentioning
confidence: 95%